The Perceptions of EFL Students on the Use of iPusnas Applications in Finding Resources for English Academic Writing - Chindy Yulia Permatasari; Syafryadin Syafryadin (English Education Study Program Faculty of Teacher Training and Education, 2023)
This research aims to determine the perceptions of EFL students regarding using the iPusnas application to find English language resources and determine the level of utilization of the iPusnas application as a reference for academic writing. To achieve the objectives of this study, 34 students majoring in English at the Fatmawati Sukarno Bengkulu State Islamic University were selected as the research sample. The questionnaire instrument was used to collect data in this study. A total of 22 questions were divided into 12 questions for the variable perception of using iPusnas to find English sources based on three aspects of perception: cognition, affection, and conation. On the other hand, 10 other questions are to find out the use of the iPusnas application as a reference source for academic writing, which consists of 6 indicators based on The Big 6 theory (Process of Solving Information Problems). Then the data obtained were analyzed using a quantitative descriptive approach with the tabulation stage and data analysis using the Likert scale technique. Furthermore, based on the data processing analysis findings, this study's results indicate that perceptions of using the iPusnas application to search for English sources rank very well with an interval scale of 3.72 (Very Good). The results of using the iPusnas application as a reference in academic writing also scored well on a scale of 3.19 (Good), indicating a high frequency of using the iPusnas application as a reference for academic writing with a score of 41 (60%). In conclusion, in this study, researchers advise students to increase the use of the iPusnas application, especially in academic writing, such as accessing the application more often to use it as a source of knowledge and not having to wait when there is a new academic writing assignment to access iPusnas.